PERCEPTIONS AND EXPERIENCES OF M-HEALTH TECHNOLOGIES AND SOCIAL MEDIA: A QUALITATIVE STUDY IN PATIENTS WITH SCHIZOPHRENIA - Pasquale Caponnetto; Maria Salvina Signorelli; Jennifer Tiralongo; Alessandro Rodolico; Carmen Concerto; Antonino Petralia; Lucio Inguscio (Health Psychology Research)
The growing influence of technology in the realm of mental health presents promising prospects for patients with psychiatric disorders like schizophrenia. The objective of this study is to investigate the perceptions of individuals with schizophrenia spectrum disorder regarding the utilization of technology and social media. The qualitative methodology used consists of an individual structured interview and the data were subjected to thematic analysis. The results show that the participants use digital tools for various activities such as work, searching for information, entertainment, and socialising. Their perceptions confirm the usefulness and easy accessibility of these tools, which enable positive changes in the organisation of daily life and social relationships. In general, it is possible to identify both positive and negative aspects of technology and social media, such as abuse and addictive behaviour, network and information overload problems, and the risk that privacy may not be guaranteed; among the positive ones, the promotion of remote sociability, speed in carrying out tasks and acquiring useful information emerge. Most of the participants express a positive perception of the possibility that digital tools can help in the field of mental health.